A metal lithium negative electrode and its preparation method and application
By using a metal lithium negative electrode with a multi-alloy phase structure in metal lithium batteries, and using the combination of the framework phase and functional phase, the problems such as volume effect and uneven deposition in metal lithium batteries are solved, and long cycle life and large-scale charging and discharge are achieved and high security.
Patent Information
- Application Number
- CN202411479574.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-10-23
AI Technical Summary
The prior art is difficult to solve the problems of volume effect, uneven deposition, poor safety and poor cycle stability in metal lithium batteries, which makes it difficult to commercialize metal lithium in practical applications.
The metal lithium negative electrode adopts a multi-alloy phase structure, including the framework phase and the functional phase. The skeleton phase is formed of boron, silicon or tin and lithium, and the functional phase is formed of indium, tin, silver, magnesium, selenium or bismuth and lithium. Through a specific mass ratio and structural design, the deposition and peeling of metal lithium are regulated, and the circulation performance is improved. Rate performance.
The long cycle life and large-scale charging and discharging capacity of metal lithium negative electrodes are achieved, the safety and energy density of the battery are improved, and the problems of volume expansion and uneven deposition are solved.
Smart Images

Figure CN119181770B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of lithium batteries, and in particular to a metal lithium negative electrode. Background Art
[0002] In recent years, with the rise and rapid development of the electric vehicle industry, people's demand for power batteries has also increased. Due to the large demand for power high-energy density batteries in the market, traditional positive electrode materials such as lithium iron phosphate, lithium manganese oxide and lithium nickel cobalt aluminum oxide, combined with traditional negative electrode materials such as graphite and silicon-based materials, cannot meet actual needs, so a new battery system needs to be developed. Among them, metallic lithium, as the next generation of highly potential high-energy specific negative electrode materials, has attracted widespread attention.
[0003] However, although researchers have done a lot of preliminary basic work and studied various methods of modifying lithium metal and the relationship between structure and properties, they are still unable to overcome two or more of the problems such as volume effect, uneven deposition of lithium metal, poor safety and poor cycle stability at the same time in actual large-scale applications. Therefore, at this stage, few battery manufacturers can directly use lithium metal as a commercially viable negative electrode material, which seriously affects the promotion and development of lithium metal in practical application fields.
[0004] With the deepening of research, alloying can solve the above-mentioned problems of metallic lithium to a certain extent. For example, CN109244473A discloses a lithium alloy strip and a preparation method thereof, wherein the alloy strip contains a uniformly mixed metallic lithium element and a transition metal element with a micro-nano structure; the transition metal is at least one of copper, nickel, scandium, titanium, vanadium, chromium, manganese, cobalt and niobium, and the metallic lithium element is filled in the transition metal element with a mesh structure. The strength and hardness of the lithium alloy strip are better than those of metallic lithium, but the added transition metal has poor affinity for metallic lithium and cannot induce uniform deposition of metallic lithium.
[0005] Dongping Chen et al. prepared a Li-B-Zn ternary alloy by melting method (Dongping Chen, PiaoQing, Fengcheng Tang, et. al, A Self-Supported Hierarchic 3D Double SkeletonHost for Highly Stable Lithium Metal Batteries, Mater. Today Energy. (2023)101272.DOI: 10.1016 / j.mtener.2023.101272). Although the introduction of Zn improves the lithium affinity, the improvement on the diffusion of metallic lithium in the negative electrode is limited, and the rate performance is poor, which cannot meet the needs of the drone market.
[0006] Based on this, how to develop and design a negative electrode material for metal lithium batteries with long cycle and high rate charge and discharge has become an urgent problem that needs to be solved. Summary of the invention
[0007] In order to solve the problems existing in the prior art, the present invention proposes a metal lithium negative electrode and a preparation method and application thereof, which simultaneously solves the problems of uneven deposition and volume expansion during the charging and discharging process of metal lithium, and has good safety and excellent cycle performance and rate performance.
[0008] The present invention provides a metallic lithium negative electrode, which comprises metallic lithium and a multi-element alloy phase distributed in the metallic lithium, wherein the multi-element alloy phase comprises a skeleton phase and a functional phase, wherein the skeleton phase comprises a skeleton alloy formed by elements of boron, silicon or tin and lithium, and the functional phase comprises a functional alloy formed by at least one of the elements of indium, tin, silver, magnesium, selenium or bismuth and lithium, wherein when the skeleton alloy is a boron-lithium alloy, the functional alloy is an alloy formed by at least one of indium, tin, selenium or bismuth and lithium; when the skeleton alloy is a tin-lithium alloy, the functional alloy is an alloy formed by silver and lithium; when the skeleton alloy is a silicon-lithium alloy, the functional alloy is an alloy formed by magnesium and lithium, wherein, based on the mass of the lithium alloy negative electrode being 100%, the mass of the skeleton phase is ≤10% and the mass of the functional phase is ≤20%.
[0009] In the present invention, an alloy formed by boron and / or silicon and / or tin and lithium is used as a skeleton phase, which can not only release part of the lithium during the charging process and can be used as a negative electrode material, but also retain the skeleton structure of the alloy phase, playing a dual role of stabilizing the negative electrode structure of metallic lithium and inducing uniform deposition of metallic lithium. On the other hand, the functional phase reduces the deposition potential of metallic lithium, and the diffusion of metallic lithium in the functional phase is relatively fast, which can quickly guide the deposition and diffusion of metallic lithium, inhibit the generation and growth of lithium dendrites, and meet the needs of high-rate charge and discharge. The skeleton phase and the functional phase cooperate with each other with a specific mass content, jointly regulate the deposition and stripping of metallic lithium, and improve the cycle performance and rate performance of the lithium battery.
[0010] Optionally, the skeleton phase includes elemental boron, which can form an alloy with metallic lithium. The lithium-boron alloy itself is a porous structure that can store lithium and functional phases, and can also provide space for the volume expansion of metallic lithium. In the discharge process, the lithium desorption potential is lower than that of metallic lithium, and the metallic lithium in the negative electrode is preferentially desorbed. The alloy plays a role in stabilizing the negative electrode structure. As the potential continues to increase, part of the lithium in the alloy is slowly desorbed, and part is not desorbed. The remaining alloy can serve as a skeleton to stabilize the negative electrode and alleviate the volume expansion problem of metallic lithium. During the charging process, the alloy phase can also play a role in regulating the deposition of metallic lithium.
[0011] Optionally, taking the mass of the lithium alloy negative electrode as 100%, the mass of the skeleton phase is ≤10%, for example, it can be 0.1%, 0.5%, 1%, 2%, 3%, 5%, 8%, 9% or 10%, including but not limited to the listed point values. If the mass of the skeleton phase is too low, the effect of stabilizing the negative electrode structure is limited. If the mass of the skeleton phase is too high, more inactive substances are introduced, which is not conducive to obtaining a high specific energy lithium metal battery. In addition, the hardness of the lithium alloy is too high, and the processing performance deteriorates, preferably 1-5%.
[0012] Optionally, the functional phase includes at least one of indium, silver, tin, bismuth or selenium. The elements in the functional phase can better induce metal lithium deposition, and the atomic radius is larger than that of metal lithium, and metal lithium diffuses faster, which is conducive to high-rate charge and discharge of metal lithium batteries.
[0013] Optionally, taking the mass of the lithium alloy negative electrode as 100%, the mass of the functional phase is ≤20%, for example, it can be 0.1%, 0.5%, 1%, 3%, 5%, 8%, 10%, 12%, 15%, 18% or 20%, etc., including but not limited to the listed point values. If the mass of the functional phase is too low, the effect on the deposition regulation of metallic lithium is limited. If the mass of the functional phase is too high, more inactive substances are introduced, which is not conducive to obtaining a high specific energy lithium metal battery, and it is difficult to distribute evenly, which is not conducive to cooperation with the skeleton phase. The preferred range is 1-10%.
[0014] Optionally, the mass ratio of the skeleton phase to the functional phase is in the range of (0.05-50):1, for example, it can be 0.05:1, 0.08:1, 0.1:1, 0.15:1, 0.3:1, 0.5:1, 1:1, 2:1, 4:1, 5:1, 7:1, 10:1, 15:1, 20:1, 30:1, 40:1 or 5:1, etc., including but not limited to the listed point values. If the mass ratio is too small, the skeleton phase is too small, and the effect on the structural stability of the negative electrode and the uniform deposition and regulation of the storage functional phase and metallic lithium is limited; if the mass ratio is too large, the skeleton phase is too much, the processing performance of the negative electrode is deteriorated, and it is difficult to achieve below 50μm, and the energy density of the negative electrode is low, which does not meet the actual requirements of high specific energy batteries, and is preferably (0.1-10):1.
[0015] Optionally, the thickness of the lithium alloy negative electrode is 1-100 μm, preferably 5-50 μm.
[0016] Optionally, the metallic lithium negative electrode can be used alone or laminated on a current collector.
[0017] Optionally, the current collector includes copper foil, perforated copper foil, textured copper foil, stainless steel foil, nickel foil or a carbon material current collector.
[0018] The present invention also provides a method for preparing the metal lithium negative electrode as described above, which comprises the following steps:
[0019] 1) Heat the lithium metal to 200-300°C and keep it warm (e.g., 2 hours);
[0020] 2) Add skeleton phase alloy elements, raise the temperature to 400-600°C, and keep it warm for a period of time (e.g. 2 hours);
[0021] 3) Add functional phase alloy elements and keep warm for a period of time (e.g. 4 hours);
[0022] 4) Cool down to 200~300℃ and cast;
[0023] 5) Pressure rolling or heating coating to the required thickness.
[0024] Optionally, in an inert atmosphere such as argon, a lithium ingot is melted at a temperature above 200°C into liquid lithium, and then materials containing a skeleton phase and a functional phase are added. The temperature is increased or not increased depending on the melting state of the materials. The temperature of the increased temperature is preferably such that all the materials are in liquid state. The materials are stirred and fully mixed, and kept warm. Then, the temperature is reduced naturally or by gradient cooling to form an alloy material. Finally, a lithium alloy negative electrode is made by mechanical rolling or coating.
[0025] The present invention also provides a metal lithium battery comprising the metal lithium negative electrode as described above.
[0026] Optionally, the metal lithium battery includes at least one of a soft-pack metal lithium battery, a cylindrical metal lithium battery, or a button metal lithium battery. The metal lithium battery can be a laminated battery or a wound battery.
[0027] Compared with the prior art, the present invention has at least the following beneficial effects:
[0028] (1) The metallic lithium negative electrode provided by the present invention is a lithium alloy negative electrode of a specific composition. The skeleton phase in the lithium alloy negative electrode can solve the problems of volume expansion and uneven deposition of metallic lithium at the same time, and has good cycle performance; the functional phase in the lithium alloy negative electrode can quickly guide the deposition and diffusion of metallic lithium, inhibit the generation and growth of lithium dendrites, and meet the requirements of high-rate charge and discharge.
[0029] (2) The metal lithium negative electrode provided by the present invention is a lithium alloy negative electrode of a specific composition. The skeleton phase has a porous structure and can store lithium and functional phase, thus playing a good role in stabilizing the negative electrode. The skeleton phase and functional phase cooperate with each other to jointly improve the cycle performance, rate performance and safety of the metal lithium battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1These are the test curves of Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3. DETAILED DESCRIPTION
[0031] In order to make the purpose, technical scheme and advantages of the present invention clearer, the features and other aspects of the present invention are described in more detail in conjunction with the embodiments. It should be understood that the described features and other aspects can be implemented in any suitable manner and in any suitable number combination without exceeding the scope of the present invention. Detailed features are mentioned in the specific embodiments to better understand the present invention, but it should be understood that these features are only used for explanation and not as a limitation on the scope of the invention. In addition, in order to better describe the present invention, the terms "including", "covering" and the like used herein should be understood in a broad sense without becoming the meaning of the terms. For ordinary technicians in this technical field, the specific meanings of the above terms in this application can be understood according to the specific circumstances. Unless otherwise specified, the directional words such as "upper", "lower", "left", "right" and the like used in this specification refer only to the relative orientation of an embodiment of the specification when it is used, and cannot be understood as an absolute limitation of the upper and lower, left and right, etc. of an embodiment of the specification. Unless otherwise defined, all technical and scientific terms used in this specification have the meanings generally understood by ordinary technicians in the technical field to which the present invention belongs, and the illustrative meaning of the words is considered appropriate except for the explicit definition of the meaning different from that described in this specification.
[0032] Example 1
[0033] This embodiment provides a metal lithium negative electrode, wherein the metal lithium negative electrode is a lithium boron indium negative electrode with a thickness of 100 μm, the mass fraction of boron is 1%, and the mass fraction of indium is 2%. The metal lithium negative electrode is assembled into a symmetrical battery. The battery model is 2025, and the electrolyte is purchased from KLD-FS09 (1.0M LiFSI in FEC:DME=3:1 vol%), and the injection amount is 1g.
[0034] The preparation method of the lithium-boron-indium negative electrode comprises the following steps: (1) in an argon environment, heating a lithium ingot in a heating furnace at 250°C to melt it into liquid lithium, adding indium particles and boron powder while heating and stirring, raising the temperature to 600°C, and keeping the temperature for 10 hours until the indium particles and boron powder disappear, stopping heating, and slowly cooling to make an alloy ingot, and then using a mechanical rolling process and equipment to make a lithium-boron-indium negative electrode.
[0035] Under the condition of 25℃±2℃, the test is stopped when the capacity of the metal lithium symmetric battery is 2mAh, the test current is 2mA, and the test curve is as follows: Figure 1 As shown, from Figure 1It can be seen that the metal lithium battery can be cycled for 660 hours and has good cycle stability.
[0036] Example 2
[0037] Compared with Example 1, the only difference is that the mass fraction of boron in the negative electrode is 5%, and the other conditions remain the same.
[0038] Example 3
[0039] Compared with Example 1, the only difference is that the mass fraction of indium in the negative electrode is 10%, and the other conditions remain the same.
[0040] Example 4
[0041] Compared with Example 1, the only difference is that the lithium boron indium negative electrode is replaced by a lithium tin silver negative electrode, the mass fraction of tin is 1%, the mass fraction of silver is 2%, and the other conditions remain the same.
[0042] Example 5
[0043] Compared with Example 1, the only difference is that the lithium boron indium negative electrode is replaced by a lithium silicon magnesium negative electrode, the mass fraction of silicon is 1%, the mass fraction of magnesium is 2%, and the other conditions remain the same.
[0044] Example 6
[0045] Compared with Example 1, the only difference is that the lithium boron indium negative electrode is replaced by a lithium boron selenium negative electrode, the mass fraction of boron is 1%, the mass fraction of selenium is 2%, and the other conditions remain the same.
[0046] Example 7
[0047] Compared with Example 1, the only difference is that the lithium boron indium negative electrode is replaced by a lithium boron tin negative electrode, the mass fraction of boron is 1%, the mass fraction of tin is 2%, and the other conditions remain unchanged.
[0048] Example 8
[0049] Compared with Example 1, the only difference is that the lithium boron indium negative electrode is replaced by a lithium boron bismuth negative electrode, the mass fraction of boron is 1%, the mass fraction of bismuth is 2%, and the other conditions remain unchanged.
[0050] Example 9
[0051] Compared with Example 1, the only difference is that the mass fraction of boron in the negative electrode is 0.1%, and the other conditions remain the same.
[0052] Example 10
[0053] Compared with Example 1, the only difference is that the mass fraction of indium in the negative electrode is 0.1%, and the other conditions remain the same.
[0054] Comparative Example 1
[0055] Compared with Example 1, the only difference is that the negative electrode is a pure lithium strip.
[0056] Comparative Example 2
[0057] Compared with Example 1, the only difference is that the negative electrode is a lithium-tin alloy, and the mass fraction of tin is 2%.
[0058] Comparative Example 3
[0059] Compared with Example 1, the only difference is that the negative electrode is a lithium-boron alloy and the mass fraction of boron is 1%.
[0060] Comparative Example 4
[0061] Compared with Example 1, the only difference is that the lithium boron indium negative electrode is replaced by a lithium silver indium negative electrode, the mass fraction of silver is 1%, the mass fraction of indium is 2%, and the other conditions remain unchanged.
[0062] Comparative Example 5
[0063] Compared with Example 1, the only difference is that the lithium boron indium negative electrode is replaced by a lithium boron zinc negative electrode, the mass fraction of boron is 1%, the mass fraction of zinc is 2%, and the other conditions remain unchanged.
[0064] Table 1
[0065]
[0066] From Table 1, we can see that:
[0067] (1) Comparative Examples 1 to 3 show that the metal lithium negative electrodes prepared by controlling the appropriate ratio of the skeleton phase and the functional phase of lithium boron indium all have excellent electrochemical properties.
[0068] (2) By comparing Example 1 and Example 4 to Example 8, it can be seen that by controlling the appropriate skeleton phase elements and functional phase elements, the prepared metal lithium negative electrodes all have excellent electrochemical properties.
[0069] (3) By comparing Example 1, Example 9 and Example 10, it can be seen that the cycle performance of the metallic lithium negative electrode in Example 1 is better than that in Examples 9 and 10. This is because the boron content as the skeleton phase in Example 1 is relatively high, which is beneficial to stabilizing the negative electrode structure, and the indium content is relatively high, which is beneficial to induction of uniform deposition of metallic lithium by indium; the boron content in Example 9 is relatively low, and the effect of stabilizing the negative electrode structure is limited; the functional phase indium content in Example 10 is relatively low, and the induction deposition effect is limited.
[0070] (4) By comparing Example 1 with Comparative Example 1, it can be seen that the cycle performance of the metal lithium negative electrode in Comparative Example 1 is poor. This is because the pure lithium negative electrode has neither a skeleton phase nor a functional phase, and has poor cycle performance.
[0071] (5) By comparing Example 1 with Comparative Example 2, it can be seen that with only a pure skeleton phase, the performance is improved with a purer lithium negative electrode, but it is still relatively poor.
[0072] (6) By comparing Example 1 with Comparative Example 3, it can be seen that with only a simple functional phase, the performance is improved with a purer lithium negative electrode, but it is still relatively poor, and the effect of the functional phase is lower than that of the skeleton phase. This is because the stability of the metallic lithium negative electrode structure is more important.
[0073] (7) By comparing Example 1 with Comparative Example 4, it can be seen that with only a single functional phase, even a ternary functional phase alloy, the performance improvement is relatively limited.
[0074] (8) By comparing Example 1 with Comparative Example 5, it can be seen that the selection of functional phase and skeleton phase elements is inappropriate, and the performance improvement is relatively limited.
Claims
1. A metallic lithium negative electrode, comprising metallic lithium and a multi-element alloy phase distributed in the metallic lithium, wherein the multi-element alloy phase comprises a skeleton phase and a functional phase, wherein the skeleton phase comprises a skeleton alloy formed by elements of boron, silicon or tin and lithium, and the functional phase comprises a functional alloy formed by at least one of elements of indium, tin, silver, magnesium, selenium or bismuth and lithium, wherein: When the skeleton alloy is a boron-lithium alloy, the functional alloy is an alloy formed by lithium and at least one of indium, tin, selenium or bismuth; when the skeleton alloy is a tin-lithium alloy, the functional alloy is an alloy formed by silver and lithium; when the skeleton alloy is a silicon-lithium alloy, the functional alloy is an alloy formed by magnesium and lithium, wherein, based on the mass of the lithium alloy negative electrode as 100%, the mass of the skeleton phase is ≤10% and the mass of the functional phase is ≤20%.
2. The metallic lithium negative electrode according to claim 1, characterized in that Taking the mass of the lithium alloy negative electrode as 100%, the mass of the skeleton phase is 1-5%; and the mass of the functional phase is 1-10%.
3. The metallic lithium negative electrode according to claim 1, characterized in that The mass ratio of the skeleton phase to the functional phase is in the range of (0.05-50):
1.
4. The metallic lithium negative electrode according to claim 1, characterized in that The mass ratio of the skeleton phase to the functional phase is (0.1-10):
1.
5. The metal lithium negative electrode according to claim 1, characterized in that The thickness of the lithium alloy negative electrode is 1-100 μm.
6. The metallic lithium negative electrode according to claim 1, characterized in that The metal lithium negative electrode is used alone or coated on a current collector.
7. The metallic lithium negative electrode according to claim 6, characterized in that The current collector includes copper foil, perforated copper foil, textured copper foil, stainless steel foil, nickel foil or carbon material current collector.
8. A method for preparing a metallic lithium negative electrode as claimed in any one of claims 1 to 7, comprising the following steps: Heat the lithium metal to 200-300°C and keep it warm; Add skeleton phase alloy elements, raise the temperature to 400-600℃, and keep it warm for a while; Add functional phase alloy elements and keep warm for a period of time; Cool down to 200~300℃ and cast; Pressure rolling or heat coating to the required thickness.
9. Use of the metal lithium negative electrode according to any one of claims 1 to 7 in a metal lithium battery, characterized in that: The metal lithium battery includes at least one of a soft-pack metal lithium battery, a cylindrical metal lithium battery or a button metal lithium battery.
Citation Information
Patent Citations
A lithium alloy strip and a preparation method thereof
CN109244473A
Secondary lithium battery negative electrode with characteristic of lithium dendrite generation inhibition
CN103972470A
Lithium metal alloy negative electrode material and preparation method and application thereof
CN110120502A